Historical conditions of ICETEX emergence in Colombia - Sol Alejandra Calderón Patiño; Cirly Uribe Ochoa (Cogent Social Sciences)
This study explores the socio-political, economic and educational context in which the Instituto Colombiano de Crédito Educativo y Estudios Técnicos en el Exterior (Colombian Institute of Educational Credit and Technical Studies Abroad) was created. Studying the historical conditions allows us to answer the questions of why and how this institution arose in Colombia. Based on the Foucauldian assumptions on genealogy and the conditions of possibility, the study of this institution proposes its emergence to be an effect of several elements, which are approached critically. To this end, the article is divided into two sections wherein the idea of the creation of the Institute and the experiences it went through are analysed, to then deal with the materialisation of this idea in relation to the conditions of the Colombian environment.